2011
DOI: 10.1111/j.1524-4725.2011.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Dermatology for Aging Ethnic Skin

Abstract: With the proper knowledge of how to treat aging skin of color, these patients can experience the benefits of cosmetic procedures while minimizing the risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…2) and its appearance is quite distinct from predominantly intrinsically aged skin (Farage, 2008;Fisher et al, 2002). The severity of photoaging also depends on the skin type, being more prominent in fair skin individuals (skin types I and II) and less noticeable in people with skin type III or higher Davis and Callender, 2011).…”
Section: Extrinsic Agingmentioning
confidence: 98%
See 1 more Smart Citation
“…2) and its appearance is quite distinct from predominantly intrinsically aged skin (Farage, 2008;Fisher et al, 2002). The severity of photoaging also depends on the skin type, being more prominent in fair skin individuals (skin types I and II) and less noticeable in people with skin type III or higher Davis and Callender, 2011).…”
Section: Extrinsic Agingmentioning
confidence: 98%
“…These symptoms may vary per body site. It has been observed that the Page 4 of 53 A c c e p t e d M a n u s c r i p t 4 intrinsic aging process differs per ethnic group (Davis and Callender, 2011), probably caused by the degree of pigmentation, and possibly more not yet identified contributing factors. Skin that is aged only by intrinsic factors does actually not exist.…”
Section: Intrinsic Agingmentioning
confidence: 99%
“…Deep chemical peels should generally be avoided in darker skin types because of the risk of postpeel complications such as dyspigmentation, keloid formation, and hypertrophic scarring. [1] Peeling agents, when applied to the skin create a superficial wound by exfoliating the epidermis or dermis, which subsequently reepithelizes along with remodelling of underlying collagen leading to improvement in dyschromia, photodamage, and rhytides.…”
Section: Chemical Peelsmentioning
confidence: 99%
“…[1] These lasers are not commonly used in dark skin color because of the greater risk of complications such as dyschromia and scarring. Other side effects include erythema, reactivation of herpes virus and other bacteria.…”
Section: Ablative Laser Resurfacingmentioning
confidence: 99%
“…Other treatments associate with several adverse effects e.g. laser treatment may lead to thermal injury and post-inflammatory hyperpigmentation [12] . Also, despite the popularity of using over-the-counter topical formulations for mending photoaged skin, the evidence for their clinical efficacy and mechanism of action is often limited [13] .…”
Section: Introductionmentioning
confidence: 99%